Aliphatic-aromatic polyester as well as preparation method and application thereof

By using the preparation method of the fat-aromatic polyester in polyester materials, the existing materials are difficult to have the problem of high transparency and toughness, and the high transparency rate and high toughness of high-thickness conditions are realized, expanding The application space of polyester materials.

CN119350604AActive Publication Date: 2025-01-24CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310909036.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-01-24
Estimated Expiration
2043-07-24

AI Technical Summary

Technical Problem

Existing polyester materials are difficult to combine high transparency and toughness, and cannot meet application areas with high toughness requirements.

Method used

Using the aliphed-aromatic polyester, it mixes the first phase of the reactions of the fats dual alcohol, aromatic monomer and catalyst under the esterization reaction conditions to obtain a prefabrication, and then perform under the condition of concentration reaction conditions under the condition of retractable reaction conditions The second stage reaction is prepared to prepare polyester with high light and toughness.

Benefits of technology

The high light transmission rate (greater than 90 %) and high toughness of polyester materials under high thickness conditions (more than 50-1050 %) meet the application requirements of optical membrane, outer packaging membrane or polymer glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350604A_ABST
    Figure CN119350604A_ABST
Patent Text Reader

Abstract

The invention relates to a polyester material, and discloses aliphatic-aromatic polyester as well as a preparation method and application thereof. The light transmittance of the aliphatic-aromatic polyester is greater than 90% when the thickness of the aliphatic-aromatic polyester is 5-100mm, and the elongation at break of the aliphatic-aromatic polyester is 50-1050%. The preparation method comprises the following steps: (1) under an esterification reaction condition, mixing an aliphatic dihydric alcohol monomer containing a structure as shown in a formula (I), an aromatic monomer containing a structure as shown in a formula (II) and a catalyst, and then carrying out a first-stage reaction to obtain a prepolymer; and (2) carrying out a second-stage reaction on the prepolymer under a polycondensation reaction condition. The aliphatic-aromatic polyester not only has good toughness, but also has good light transmittance performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to polyester materials, in particular to an aliphatic-aromatic polyester and a preparation method and application thereof. Background Art

[0002] At present, the commonly used optical-grade transparent polymers on the market include biaxially oriented polyester film (BOPET), polystyrene (PS), polycarbonate (PC) and polymethyl methacrylate (PMMA). Due to their good transparency (light transmittance greater than 85%), they have become the most important strategic materials in the optoelectronics industry chain. However, the structure of BOPET, PS, PC and PMMA materials contains a large number of benzene rings or side methyl rigid groups, and the toughness of the materials is poor (elongation at break is less than 10%). For application fields with high toughness requirements, it is difficult to meet the performance requirements. Moreover, ordinary PET is a semi-crystalline polyester. After a special process of biaxial stretching (BO), the orientation and crystallization microstate of the material are changed, so that the light transmittance of BOPET can reach more than 88% to meet the optical requirements of the optical base film.

[0003] CN109320699A discloses a thermoplastic aliphatic-aromatic copolyester elastomer, which is obtained by polymerizing 1,4-butanediol monomer, aliphatic dibasic acid monomer and 4,4'-diphenyl ether dicarboxylic acid or 4,4'-diphenyl ether dimethyl ester monomer. However, the transparency of the obtained material needs to be improved.

[0004] Most of the windows and display cabinets in the prior art are still made of glass materials. Common glass is organic glass (polymethyl methacrylate) and inorganic glass. Regardless of organic glass or inorganic glass, its elongation at break is basically relatively low (for example, the elongation at break of organic glass is only 2-3%), resulting in low toughness, brittleness and easy to break. It is easy to break when used as a window or display cabinet, increasing the replacement cost. Although some polymer materials meet the toughness requirements and are not easy to break, their light transmittance does not meet the requirements and cannot be used for windows and display cabinets. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem that polyester materials in the prior art are difficult to have both transparency and toughness, and to provide an aliphatic-aromatic polyester and a preparation method and application thereof. The aliphatic-aromatic polyester has high toughness and good light transmittance under high thickness conditions.

[0006] In order to achieve the above object, the first aspect of the present invention provides an aliphatic-aromatic polyester, wherein the light transmittance of the aliphatic-aromatic polyester is greater than 90% when the thickness is 5-100 mm, and the elongation at break of the aliphatic-aromatic polyester is 50-1050%.

[0007] The second aspect of the present invention provides a method for preparing an aliphatic-aromatic polyester, comprising the following steps:

[0008] (1) under esterification reaction conditions, an aliphatic diol monomer having a structure represented by formula (I), an aromatic monomer having a structure represented by formula (II) and a catalyst are mixed and then subjected to a first stage reaction to obtain a prepolymer;

[0009]

[0010] R1 is a C4-C8 alkylene group, and R2, R3, R4, R5, R6, R7, R8 and R9 are each independently a C1-C4 alkyl group or hydrogen;

[0011] (2) Under polycondensation conditions, the prepolymer is subjected to a second stage reaction.

[0012] The third aspect of the present invention provides the use of the above-mentioned aliphatic-aromatic polyester or the aliphatic-aromatic polyester prepared by the above-mentioned preparation method in optical films, outer packaging films or polymer glass.

[0013] The light transmittance of the polyester piece with a thickness of 5-100 mm after hot pressing of the aliphatic-aromatic polyester provided by the present invention is greater than 90%, indicating that the polyester has good light transmittance under high thickness conditions; the elongation at break of the aliphatic-aromatic polyester is 50-1050%, indicating that the polyester has good toughness. The aliphatic-aromatic polyester can meet the requirements of high transparency and toughness.

[0014] Moreover, the strength and elongation at break of aliphatic-aromatic polyesters can be adjusted by adjusting the number of methylene groups in the aliphatic diol structural unit, thereby obtaining polyester materials that meet different usage requirements. They can be used as optical films, packaging bags, window glass, display cabinet glass, etc., further expanding the application space of polyester materials.

[0015] The preparation method provided by the present invention prepares aliphatic-aromatic polyester by subjecting monomers to esterification reaction and polycondensation reaction at one time, which is simple to operate, has strong process controllability, and is easy to realize industrialization of the product. Moreover, the prepared polyester can take into account both light transmittance and toughness, thus expanding a new method for preparing polyester materials taking into account both light transmittance and toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the infrared spectrum of the aliphatic-aromatic polyester prepared in Example 1;

[0017] Figure 2 is the wide-angle X-ray diffraction spectrum of the aliphatic-aromatic polyester prepared in Example 1;

[0018] Figure 3 is the DSC melting curve of the aliphatic-aromatic polyester prepared in Example 1;

[0019] Figure 4 is the stress-strain curve of the aliphatic-aromatic polyester prepared in Example 1. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] As mentioned above, the first aspect of the present invention provides an aliphatic-aromatic polyester, wherein the light transmittance of the aliphatic-aromatic polyester is greater than 90% when the thickness is 5-100 mm, and the elongation at break of the aliphatic-aromatic polyester is 50-1050%.

[0022] The light transmittance of the polyester piece with a thickness of 5-100 mm after hot pressing of the aliphatic-aromatic polyester provided by the present invention is greater than 90%, indicating that the polyester has good light transmittance under high thickness conditions; the elongation at break of the aliphatic-aromatic polyester is 50-1050%, indicating that the polyester has good toughness and can be used as optical glass.

[0023] Preferably, the light transmittance of the aliphatic-aromatic polyester is greater than 90% when the thickness is 30-100 mm. Polyester meeting this condition can be better applied to window glass and display cabinet glass.

[0024] In the present invention, polyester is made into a sheet with a thickness of 5-100 mm by hot pressing, and then cut into a size of 2 cm×5 cm. The air transmittance is used as a reference, and the transmittance corresponding to a wavelength of 550 nm is read using a UV-1911i spectrophotometer from Shimadzu Corporation of Japan, which is the transmittance of the polyester at this thickness.

[0025] In the present invention, the synthesized aliphatic-aromatic polyester is made into a sample with a thickness of 1 mm by hot pressing, and then a dumbbell-shaped cutter (type 4 dumbbell-shaped cutter in GB / T 528-2009 standard) is used to make a sample strip with a thickness of 1 mm and a width of 4 mm in the narrow part. The test is carried out using Shenzhen Kaiqiangli WD-II 10 electronic universal testing machine at a tensile rate of 50 mm / min according to GB / T 1040-1992, and the elongation multiple at break is the elongation at break of the aliphatic-aromatic polyester.

[0026] Preferably, the crystallinity of the aliphatic-aromatic polyester is less than or equal to 0.4%, indicating that the polyester has good light transmission performance and has better application in optical glass. In order to further improve the light transmission performance of the aliphatic-aromatic polyester, it is further preferred that the crystallinity of the aliphatic-aromatic polyester is less than or equal to 0.1%. More preferably, the crystallinity of the aliphatic-aromatic polyester is 0.

[0027] According to the present invention, the crystallinity is measured according to the method shown in GB / T 17931-1999.

[0028] Preferably, the aliphatic-aromatic polyester provided by the present invention has a crystallinity of less than or equal to 0.4% after being stored at 25° C. for 300 days. More preferably, the aliphatic-aromatic polyester has a crystallinity of less than or equal to 0.1% after being stored at 25° C. for 300 days.

[0029] Preferably, the aliphatic-aromatic polyester is an amorphous polymer. Specifically, the aliphatic-aromatic polyester is an amorphous polymer at a temperature of 25° C. The amorphous aliphatic-aromatic polyester has better light transmission performance.

[0030] According to the present invention, preferably, the glass transition temperature of the aliphatic-aromatic polyester is 10-55° C. Further preferably, the tensile strength of the aliphatic-aromatic polyester is 2.5-25 MPa.

[0031] Preferably, the polyester is a copolyester containing a structural unit A represented by formula (I) and a structural unit B represented by formula (II),

[0032]

[0033] Wherein, R1 is a C4-C8 alkylene group, and R2, R3, R4, R5, R6, R7, R8 and R9 are each independently a C1-C4 alkyl group or hydrogen.

[0034] Specifically, R1 may be a C4-C8 straight chain alkylene group or a C4-C8 branched chain alkylene group. n may be an integer of 90 to 160. Preferably, the weight average molecular weight of the polyester is 30,000 to 50,000 g / mol.

[0035] During the research process, the inventor unexpectedly discovered that, in the absence of other structural influences, the interaction between structural unit A and structural unit B can break the crystalline structure of polyester, so that polyester presents excellent optical properties unique to the amorphous state, with high light transmittance. The light transmittance of the polyester pieces with a thickness of 5-100mm or even 30-100mm after hot pressing is >90%. And it can give the aliphatic-aromatic polyester good toughness. The efficient synergy of the structure of polyester is achieved, so that the polyester can achieve both high transparency and high toughness, and has a good application effect on optical films, outer packaging films or polymer glasses. Moreover, the strength and elongation at break of the aliphatic-aromatic polyester can be adjusted by adjusting the number of carbon (C) atoms of the structural unit A, so that a polyester material that meets different use requirements can be obtained, further expanding the application space of polyester materials.

[0036] As a specific embodiment of the present invention, R2, R3, R4, R5, R6, R7, R8 and R9 are each independently methyl or hydrogen.

[0037] Preferably, R1 is a C6-C8 branched alkylene group. The aliphatic-aromatic polyester obtained under the above conditions can better meet the requirements of both light transmittance and toughness.

[0038] The inventor unexpectedly discovered during the research that limiting the mass content of titanium in polyester to less than or equal to 0.15% can effectively improve the light transmittance of polyester. In order to further improve the long-term light transmittance of polyester, preferably, the mass content of titanium in the aliphatic-aromatic polyester is less than or equal to 0.05%. The mass content of titanium in polyester refers to the mass percentage of titanium in polyester.

[0039] The content of titanium in the aliphatic-aromatic polyester can be measured by elemental analysis. Specifically, a flame atomic absorption spectrophotometer is used to measure the titanium in the polyester.

[0040] The second aspect of the present invention provides a method for preparing an aliphatic-aromatic polyester, comprising the following steps:

[0041] (1) under esterification reaction conditions, an aliphatic diol monomer having a structure represented by formula (I), an aromatic monomer having a structure represented by formula (II) and a catalyst are mixed and then subjected to a first stage reaction to obtain a prepolymer;

[0042] in,

[0043]

[0044] R1 is a C4-C8 alkylene group, and R2, R3, R4, R5, R6, R7, R8 and R9 are each independently a C1-C4 alkyl group or hydrogen;

[0045] (2) Under polycondensation conditions, the prepolymer is subjected to a second stage reaction.

[0046] According to the present invention, the aromatic monomer is an aromatic dibasic acid and / or an aromatic dibasic acid ester. Specifically, the aromatic dibasic acid ester can be an ester formed by an aromatic dibasic acid and / or an aromatic dibasic acid and any diol in C1-C4. When the aromatic dibasic acid is used as the monomer, the end condition of the first stage reaction can be determined by the test personnel according to the actual situation, preferably, it can be determined according to the amount of water in the product. In a specific embodiment of the present invention, the end condition of the first stage reaction is: when the amount of water collected reaches 80% of the theoretical value, the esterification reaction ends. When the aromatic dibasic acid ester is used as the monomer, it can be specifically aromatic dibasic acid dimethyl ester, aromatic dibasic acid diethyl ester, aromatic dibasic acid dipropyl ester, aromatic dibasic acid dibutyl ester or other feasible aromatic dibasic acid ester compounds. Preferably, the aromatic dibasic acid ester is aromatic dibasic acid methyl ester, and the use of aromatic dibasic acid methyl ester makes the ester exchange reaction easier to carry out. The time of the first stage reaction is generally 3-4h.

[0047] The end condition of the second stage reaction can also be determined by the experimenter according to the actual situation, preferably, it can be determined according to the viscosity of the reaction system. In a specific embodiment of the present invention, the end condition of the second stage reaction is: react until the viscosity of the system no longer changes. The time of the second stage reaction is generally 3-4h.

[0048] The inventors found in the research process that the polyester prepared by the above preparation method can have good transparency and high toughness at the same time. Moreover, the method is simple to operate, has strong process controllability, and is easy to realize the industrialization of the product. A new method has been developed for preparing polyester materials with high transparency and high toughness.

[0049] In a specific embodiment of the present invention, R2, R3, R4, R5, R6, R7, R8 and R9 are each independently methyl or hydrogen.

[0050] Preferably, R1 is a C6-C8 branched alkylene group. The aliphatic-aromatic polyester obtained under the above conditions can better meet the requirements of both light transmittance and toughness.

[0051] As a specific embodiment of the present invention, the aromatic monomer is 3,3'-diphenyl ether dicarboxylic acid and / or 3,3'-diphenyl ether dicarboxylic acid dimethyl ester as an example, and its synthesis route is as follows:

[0052]

[0053] R1 is a C4-C8 alkylene group; R2, R3, R4, R5, R6, R7, R8 and R9 are each independently a C1-C4 alkyl group or hydrogen.

[0054] Preferably, the molar ratio of the aliphatic diol monomer to the aromatic monomer is 1-4:1. Under the above molar ratio conditions, the molecular weight of the polyester obtained can be guaranteed to be within an appropriate range, and the conversion rate of the reaction can be improved while ensuring the cost. In addition, the boiling point of the aliphatic diol is relatively low, which is convenient for the subsequent separation of the product and the reactant, and avoids the waste of raw materials. Further preferably, when the aromatic monomer is an aromatic dibasic acid, the molar ratio of the aliphatic diol monomer to the aromatic dibasic acid is 2-4:1; when the aromatic monomer is an aromatic dibasic acid methyl ester, the molar ratio of the aliphatic diol monomer to the aromatic dibasic acid ester is 1-1.1:1.

[0055] According to the present invention, preferably, the catalyst is a titanium-containing catalyst and / or a non-titanium-containing catalyst. Preferably, the molar ratio of the catalyst to the aromatic monomer is 0.5-1:100, specifically 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100, 1:100, or any value between the aforementioned values. Under the above molar ratio conditions, the reaction effect of the aliphatic diol monomer and the aromatic monomer can be guaranteed on the basis of the least cost. Further preferably, the catalyst is a titanium-containing catalyst and a non-titanium-containing catalyst, and the molar ratio of the titanium-containing catalyst to the non-titanium-containing catalyst is 1:1-4. Limiting the molar ratio of the titanium-containing catalyst to the non-titanium-containing catalyst within the above range can further improve the transparency of the polyester material while ensuring the catalytic effect. From the perspective of being able to further improve the transmittance of the polyester material, preferably, the mass ratio of the titanium-containing catalyst to the non-titanium-containing catalyst is 1:1-4; the titanium-containing catalyst is tetrabutyl titanate and / or tetraethyl titanate; and the non-titanium-containing catalyst is selected from at least one of stannous chloride, stannous octoate, zinc acetate and p-toluenesulfonic acid.

[0056] Preferably, in step (1), the esterification reaction conditions at least include: isolation of oxygen and a temperature of 160-180°C. Under the above conditions, aliphatic diol monomers and aromatic monomers have better esterification effects, which can make the subsequently obtained polyester have higher transparency and toughness. Isolation of oxygen is usually achieved by filling the reaction system with inert gases such as nitrogen or helium. The first stage reaction is carried out under stirring, and the stirring rate can be determined by the experimenter according to the actual situation.

[0057] Preferably, in step (2), the polycondensation reaction conditions at least include: a temperature of 220-240°C, specifically 220°C, 225°C, 230°C, 235°C, 240°C, or any value between the aforementioned values; an absolute vacuum degree of 50-80Pa, specifically 50Pa, 60Pa, 70Pa, 80Pa, or any value between the aforementioned values. Under the above conditions, the ester monomer obtained by esterification of aliphatic diol monomers and aromatic monomers has a better polycondensation effect, thereby enabling the obtained polyester to have higher transparency and toughness.

[0058] The third aspect of the present invention provides the use of the above-mentioned aliphatic-aromatic polyester or the aliphatic-aromatic polyester prepared by the above-mentioned preparation method in optical films, outer packaging films or polymer glass.

[0059] The aliphatic-aromatic polyester has good light transmittance and toughness, and has good application effect on optical films, outer packaging films or polymer glass.

[0060] According to a particularly preferred embodiment of the present invention, the method for preparing the aliphatic-aromatic polyester comprises the following steps:

[0061] (1) aliphatic diol monomer, aromatic monomer and catalyst are mixed, and the first stage reaction is carried out at a temperature of 160-180° C. under nitrogen protection and mechanical stirring. When the amount of water collected reaches 80% of the theoretical value, the first stage reaction is considered to be completed;

[0062] The structure of the aliphatic diol monomer is shown in formula (I), and the structure of the aromatic monomer is shown in formula (II).

[0063]

[0064] Wherein, R1 is a C4-C8 alkylene group; R2, R3, R4, R5, R6, R7, R8 and R9 are each independently a C1-C4 alkyl group or hydrogen.

[0065] (2) After the first stage reaction is completed, the reaction system is gradually heated to 220-240° C., the vacuum degree of the system is controlled to be 50-80 Pa, and the second stage reaction is carried out until the viscosity of the system no longer changes to obtain aliphatic-aromatic polyester.

[0066] The aliphatic-aromatic polyester prepared by the above method has good transparency and good toughness. The method is simple to operate, has strong process controllability, and is easy to realize the industrialization of the product. A new method has been developed for preparing polyester materials with both light transmittance and toughness.

[0067] The present invention will be described in detail below through examples.

[0068] In the following examples, the raw materials used were purchased from commercial sources and were all chemically pure.

[0069] (1) Infrared test: The chemical structure of the copolyester was characterized using the Avatar370 infrared spectrometer from Nicolet, USA. The total reflection mode was used during the test, and the test wave number range was 500-4000cm -1 Before the infrared test, the prepared polyester was dissolved in chloroform, and then an excess of methanol was added, and after sufficient stirring, the purified polyester was filtered and dried.

[0070] (2) XRD test: The crystal structure of the block copolyester sample was tested using an XD-3A X-ray diffractometer from Shimadzu Corporation of Japan. The sample was heat treated and the test range was 5°-50°.

[0071] (3) DSC test: The test was performed using a differential scanning calorimeter DSC8500 from PE Company of the United States. The temperature was raised from -60°C to 200°C at a rate of 10°C / min under nitrogen protection.

[0072] (4) Tensile strength at break: The synthesized aliphatic-aromatic polyester was made into a sample with a thickness of 1 mm by hot pressing, and then a dumbbell cutter (type 4 dumbbell cutter in GB / T 528-2009 standard) was used to make a sample with a thickness of 1 mm and a width of 4 mm in the narrow part. The test was carried out using Shenzhen Kaiqiangli WD-II 10 electronic universal testing machine according to GB / T 1040-1992, with a tensile rate of 50 mm / min, and the stress-strain curve of the fracture process was obtained.

[0073] (5) Light transmittance: The polyester was made into sheets with a thickness of 5-100 mm by hot pressing and then cut into sheets with a size of 2 cm × 5 cm. The light transmittance of the polyester material was tested using the UV-1911i spectrophotometer produced by Shimadzu Corporation of Japan, with the light transmittance at a wavelength of 550 nm being read, taking the light transmittance of the air as a reference.

[0074] Example 1

[0075] 0.25 mol (22.5 g) of 1,4-butanediol and 0.25 mol (78.25 g) of 3,3'-diphenylether dimethyl dicarboxylate were added to a reaction vessel, and 0.0025 mol (0.84 g) of tetrabutyl titanate was added as a catalyst. Under the conditions of N2 gas protection and mechanical stirring, the esterification reaction was carried out. The initial temperature during the reaction was 160°C, and the temperature was gradually increased to 180°C. When the amount of water collected reached 80% of the theoretical value, the esterification reaction was considered to be completed.

[0076] After the esterification reaction is completed, the reaction system is gradually heated to 240° C., the vacuum degree of the system is controlled within 50-80 Pa, and the polycondensation reaction is carried out until the viscosity of the system no longer changes to prepare the aliphatic-aromatic polyester.

[0077] from Figure 1 It can be clearly seen that the infrared spectrum of the aliphatic-aromatic polyester prepared in Example 1 is at 2945 cm -1 The characteristic absorption peak of CH bond in methylene is 1710 cm -1 The characteristic absorption peak of the C=O bond representing the presence of ester is 1150cm -1 The peak at 1594 cm is the characteristic absorption peak of CO bond. -1 and 1499cm -1 The absorption peak at corresponds to the characteristic skeleton vibration of the benzene ring. Figure 2 It is obvious that the aliphatic-aromatic polyester prepared in Example 1 has only a broad and diffuse absorption peak, indicating that these polyester films are not crystalline and have an amorphous structure. Figure 3 It can be clearly seen that the aliphatic-aromatic polyester prepared in Example 1 has a glass transition peak (T g ), but no obvious crystallization peak and melting point peak appeared, indicating that the internal arrangement of these polyester systems is amorphous and they are non-crystalline polymers. Figure 4 It can be clearly seen that the aliphatic-aromatic polyester prepared in Example 1 has a tensile strength of 23.8 MPa and an elongation at break of 50%, and has good toughness.

[0078] Example 2

[0079] 1 mol (104 g) of 1,5-pentanediol and 0.25 mol (64.5 g) of 3,3'-diphenyl ether dicarboxylic acid were added to a reaction vessel, and 0.00125 mol (0.42 g) of tetrabutyl titanate was added as a catalyst. Under the conditions of N2 gas protection and mechanical stirring, the esterification reaction was carried out. The initial temperature during the reaction was 160°C, and the temperature was gradually increased to 180°C. When the amount of water collected reached 80% of the theoretical value, the esterification reaction was considered to be completed.

[0080] After the esterification reaction is completed, the reaction system is gradually heated to 220° C., the vacuum degree of the system is controlled within 50-80 Pa, and the polycondensation reaction is carried out until the viscosity of the system no longer changes to prepare the aliphatic-aromatic polyester.

[0081] Example 3

[0082] 0.75mol (88.5g) 3-methyl-1,5-pentanediol and 0.25mol (64.5g) 3,3'-diphenyl ether dicarboxylic acid were added to the reaction vessel, and 0.00125mol (0.42g) catalyst tetrabutyl titanate was added. Under the conditions of N2 gas protection and mechanical stirring, the esterification reaction was carried out. The initial temperature during the reaction was 160°C, and the temperature was gradually increased to 180°C. When the amount of water collected reached 80% of the theoretical value, the esterification reaction was considered to be completed.

[0083] After the esterification reaction is completed, the reaction system is gradually heated to 220° C., the vacuum degree of the system is controlled within 50-80 Pa, and the polycondensation reaction is carried out until the viscosity of the system no longer changes to prepare the aliphatic-aromatic polyester.

[0084] Example 4

[0085] 0.5 mol (66 g) of 3-methyl-1,6-hexanediol and 0.25 mol (64.5 g) of 3,3'-diphenyl ether dicarboxylic acid were added to the reaction vessel, and 0.00125 mol (0.42 g) of tetrabutyl titanate catalyst was added. Under the conditions of N2 gas protection and mechanical stirring, the esterification reaction was carried out. The initial temperature during the reaction was 160°C, and the temperature was gradually increased to 180°C. When the amount of water collected reached 80% of the theoretical value, the esterification reaction was considered to be completed;

[0086] After the esterification reaction is completed, the reaction system is gradually heated to 220° C., the vacuum degree of the system is controlled within 50-80 Pa, and the polycondensation reaction is carried out until the viscosity of the system no longer changes to prepare the aliphatic-aromatic polyester.

[0087] Example 5

[0088] Aliphatic-aromatic polyester was prepared according to the method described in Example 4, except that 0.5 mol of 3-methyl-1,6-hexanediol was replaced by 0.5 mol of 2,5-dimethyl-1,6-hexanediol.

[0089] Example 6

[0090] Aliphatic-aromatic polyester was prepared according to the method described in Example 4, except that 0.25 mol of 3,3'-diphenyl ether dicarboxylic acid was replaced by 0.25 mol of 5,5'-dimethyl-3,3'-diphenyl ether dicarboxylic acid.

[0091] Example 7

[0092] Aliphatic-aromatic polyester was prepared according to the method described in Example 4, except that 0.5 mol of 3-methyl-1,6-hexanediol was replaced by 0.5 mol of 1,7-heptanediol.

[0093] Example 8

[0094] Aliphatic-aromatic polyester was prepared according to the method described in Example 2, except that tetrabutyl titanate was replaced with tetrabutyl titanate and stannous octoate in a molar ratio of 1:1.

[0095] Example 9

[0096] Aliphatic-aromatic polyester was prepared according to the method described in Example 1, except that tetrabutyl titanate was replaced with tetrabutyl titanate and zinc acetate in a molar ratio of 1:2.

[0097] Example 10

[0098] Aliphatic-aromatic polyester was prepared according to the method described in Example 2, except that tetrabutyl titanate was replaced with tetrabutyl titanate and p-toluenesulfonic acid in a molar ratio of 1:4.

[0099] Embodiment 11

[0100] Aliphatic-aromatic polyester was prepared according to the method described in Example 2, except that the molar ratio of tetrabutyl titanate to stannous octoate was 1:0.5.

[0101] Example 12

[0102] Aliphatic-aromatic polyester was prepared according to the method described in Example 2, except that the molar ratio of tetrabutyl titanate to p-toluenesulfonic acid was 1:6.

[0103] Comparative Example 1

[0104] Add 0.48mol (43.26g) of 1,4-butanediol, 0.084mol (16.99g) of 1,10-decanedioic acid and 0.036mol (10.30g) of 3,3'-diphenylether dicarboxylic acid dimethyl ester into a 250mL three-necked flask equipped with a stirring device, a condensing device and a nitrogen protection device. Add 0.0006mol (0.2g) of catalyst tetrabutyl titanate into the three-necked flask. Open the condensing water, pass N2, heat to 180℃, and after the monomer is completely melted, carry out the esterification reaction under constant temperature stirring. When the amount of water collected reaches 80% of the theoretical value, the esterification reaction is considered to be over;

[0105] After the esterification reaction is completed, the polycondensation stage begins. The condensation device is removed and replaced with a vacuum device equipped with a safety bottle, a McLaren vacuum gauge and an oil pump. The temperature is gradually raised to 220°C and the reaction is continued for 3 hours. At the same time, the vacuum degree of the system is controlled at 50-80Pa. After the polycondensation reaction is completed, the aliphatic-aromatic polyester is obtained after cooling to room temperature.

[0106] Comparative Example 2

[0107] 0.5 mol (38 g) of 1,3-propylene glycol and 0.25 mol (64.5 g) of 3,3'-diphenyl ether dicarboxylic acid were added to a reaction vessel, and 0.00125 mol (0.42 g) of tetrabutyl titanate catalyst was added. Under the conditions of N2 gas protection and mechanical stirring, the esterification reaction was carried out. The initial temperature during the reaction was 160°C, and the temperature was gradually increased to 180°C. When the amount of water collected reached at least 80% of the theoretical value, the esterification reaction was considered to be completed.

[0108] After the esterification reaction is completed, the temperature is gradually raised to 220° C., the vacuum degree of the system is controlled within 50-80 Pa, and the polycondensation reaction is carried out until the viscosity of the system no longer changes to prepare the aliphatic-aromatic polyester.

[0109] Comparative Example 3

[0110] 0.5 mol (94 g) of 1,9-nonanediol and 0.25 mol (64.5 g) of 3,3'-diphenyl ether dicarboxylic acid were added to a reaction vessel, and 0.00125 mol (0.42 g) of tetrabutyl titanate was added as a catalyst. Under the conditions of N2 gas protection and mechanical stirring, the esterification reaction was carried out. The initial temperature during the reaction was 160°C, and the temperature was gradually increased to 180°C. When the amount of water collected reached at least 80% of the theoretical value, the esterification reaction was considered to be completed.

[0111] After the esterification reaction is completed, the temperature is gradually raised to 220° C., the vacuum degree of the system is controlled within 50-80 Pa, and the polycondensation reaction is carried out until the viscosity of the system no longer changes to prepare the aliphatic-aromatic polyester.

[0112] Comparative Example 4

[0113] Aliphatic-aromatic polyester was prepared according to the method described in Example 4, except that the amount of tetrabutyl titanate added was 0.005 mol (1.68 g).

[0114] Test Example 1

[0115] The aliphatic-aromatic polyesters prepared in the above examples and comparative examples were tested for physical and chemical parameters, and the obtained parameters are shown in Table 1:

[0116] Table 1

[0117]

[0118]

[0119] The weight average molecular weight of the polyesters prepared in Examples 1-12 and Comparative Examples 1-3 is between 30000-50000 g / mol. The weight average molecular weight of the polyester prepared in Comparative Example 4 is less than 30000 g / mol.

[0120] It can be seen from the results in Table 1 that the light transmittance (550nm) of the polyester obtained in Examples 1-12 at a thickness of 5-100 mm is significantly higher than 90%, indicating that the polyester within the protection scope of the present invention has a relatively high light transmittance.

[0121] Among them, Examples 1, 2 and 7, as well as Comparative Examples 3 and 4 are polyesters prepared from straight-chain diol monomers, which have a certain degree of crystallinity after being stored at 25°C for 300 days, indicating that the straight-chain monomer has a certain influence on the long-term transparency of the polyester. Therefore, the C6-C8 branched alkylene is more conducive to the formation of polyester with long-term transparency.

[0122] From the data of Comparative Example 1, it can be seen that when the monomer contains two straight-chain diols, the glass transition temperature (-62.3°C) of the prepared polyester is lower than room temperature, and the strength of the polyester material is relatively low. From the data of Comparative Example 2, it can be seen that when the diol monomer is propylene glycol, that is, when R1 is an alkylene group with a carbon number less than 4, the carbon chain number of the aliphatic diol is relatively short, and the polyester presents obvious rigidity characteristics. Although the transparency is relatively high, the toughness is relatively poor, only 17% (elongation at break is less than 20%). From the data of Comparative Example 3, it can be seen that when the diol monomer is nonanediol, that is, when R1 is an alkylene group with a carbon number greater than 8, the carbon chain number of the aliphatic diol is relatively high, and the increased flexibility of the chain segment gives the polyester a certain toughness, but it is precisely because of the increased flexibility of the chain segment that the polyester material begins to show a crystalline state, and the transparency is significantly reduced. From the data of Example 7 and Comparative Example 4, it can be seen that when the mass content of titanium element in the catalyst is greater than 0.238%, the polyester system will be promoted to crystallize rapidly. Combining Example 2, Example 6, and Examples 8-12, it can be seen that maintaining the mass content of titanium element less than 0.05% is conducive to forming polyester with long-term transparency.

[0123] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An aliphatic-aromatic polyester, characterized in that The light transmittance of the aliphatic-aromatic polyester is greater than 90% when the thickness is 5-100 mm, and the elongation at break of the aliphatic-aromatic polyester is 50-1050%.

2. The aliphatic-aromatic polyester according to claim 1, characterized in that The light transmittance of the aliphatic-aromatic polyester is greater than 90% when the thickness is 30-100 mm.

3. The aliphatic-aromatic polyester according to claim 1 or 2, characterized in that The aliphatic-aromatic polyester has a crystallinity of less than or equal to 0.4%; Preferably, the aliphatic-aromatic polyester has a crystallinity of less than or equal to 0.1%; Preferably, the aliphatic-aromatic polyester is an amorphous polymer.

4. The aliphatic-aromatic polyester according to claim 1 or 2, characterized in that The glass transition temperature of the aliphatic-aromatic polyester is 10-55°C; Preferably, the aliphatic-aromatic polyester has a tensile strength of 2.5-25 MPa.

5. The aliphatic-aromatic polyester according to claim 1 or 2, characterized in that The polyester contains a structural unit A represented by formula (I) and a structural unit B represented by formula (II), wherein R1 is a C4-C8 alkylene group, and R2, R3, R4, R5, R6, R7, R8 and R9 are each independently a C1-C4 alkyl group or hydrogen; Preferably, R1 is a C6-C8 branched alkylene group.

6. The aliphatic-aromatic polyester according to claim 1 or 2, characterized in that The mass content of titanium in the aliphatic-aromatic polyester is less than or equal to 0.15%; Preferably, the mass content of titanium in the aliphatic-aromatic polyester is less than or equal to 0.05%.

7. A method for preparing an aliphatic-aromatic polyester, characterized in that: The steps include: (1) under esterification reaction conditions, an aliphatic diol monomer having a structure represented by formula (I), an aromatic monomer having a structure represented by formula (II) and a catalyst are mixed and then subjected to a first stage reaction to obtain a prepolymer; in, R1 is a C4-C8 alkylene group, and R2, R3, R4, R5, R6, R7, R8 and R9 are each independently a C1-C4 alkyl group or hydrogen; (2) Under polycondensation conditions, the prepolymer is subjected to a second stage reaction.

8. The preparation method according to claim 7, characterized in that: The R1 is a C6-C8 branched alkylene group.

9. The preparation method according to claim 7 or 8, characterized in that: The catalyst is a titanium-containing catalyst and / or a non-titanium-containing catalyst; Preferably, the molar ratio of the catalyst to the aromatic monomer is 0.5-1:100; Preferably, the catalyst is a titanium-containing catalyst and a non-titanium-containing catalyst, and the molar ratio of the titanium-containing catalyst to the non-titanium-containing catalyst is 1:1-4; Preferably, the titanium-containing catalyst is tetrabutyl titanate and / or tetraethyl titanate; the non-titanium-containing catalyst is selected from at least one of stannous chloride, stannous octoate, zinc acetate and p-toluenesulfonic acid; Preferably, in step (1), the esterification reaction conditions at least include: isolation of oxygen and a temperature of 160-180°C; In step (2), the polycondensation reaction conditions at least include: a temperature of 220-240° C. and an absolute vacuum of 50-80 Pa.

10. Use of the aliphatic-aromatic polyester according to any one of claims 1 to 6 or the aliphatic-aromatic polyester prepared according to the method according to any one of claims 7 to 9 in optical films, outer packaging films or polymer glass.

Citation Information

Patent Citations

  • Method for synthesizing aliphatic-aromatic copolyester

    CN103819662A

  • Thermoplastic aliphatic-aromatic copolyester elastomer and preparation method thereof

    CN109320699A

  • Method for preparing polyester copolymer having hightransparency

    KR1020020014161A